2014
DOI: 10.1155/2014/620405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Livestock Exclusion on Sidi Toui National Park Vegetation Communities, Tunisia

Abstract: The restoration technique importance resides on the assessment of its impact on biodiversity. This assessment is possible by the use of some environmental indicators extracted from a diachronic study of land cover changes in protected areas. Our study is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Generally, protected areas play an important role in carbon sequestration in arid regions (Del Rosario et al 2012;Castro et al 2015). In particular, the exclusion of livestock from the Sidi Toui National Park has increased biomass production, spatial heterogeneity, and total vegetation cover (Ould Sidi Mohamed et al 2002;Tarhouni et al 2014). Zhang (1998) reported that total canopy cover was highest in protected areas, compared with the freely grazed areas, but the short duration of his study meant he was unable to distinguish between the impacts of grazing and/or climate stress as the main cause of this variation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, protected areas play an important role in carbon sequestration in arid regions (Del Rosario et al 2012;Castro et al 2015). In particular, the exclusion of livestock from the Sidi Toui National Park has increased biomass production, spatial heterogeneity, and total vegetation cover (Ould Sidi Mohamed et al 2002;Tarhouni et al 2014). Zhang (1998) reported that total canopy cover was highest in protected areas, compared with the freely grazed areas, but the short duration of his study meant he was unable to distinguish between the impacts of grazing and/or climate stress as the main cause of this variation.…”
Section: Discussionmentioning
confidence: 99%
“…Five dominant native perennial species were selected, because they are key species of the five main plant communities in the park and its surrounding (Ould Sidi Mohamed et al 2002;Tarhouni et al 2014): A. henoniana, G. decander, R. suaveolens, H. schmittianum and H. scoparium. The biomass and canopy cover of these species were measured during the spring of 2017, 2018 and 2019, respectively.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…These problems are generally compounded by anthropogenic factors such as overgrazing and wood harvesting (Le Houérou, 2009). Taken together, these factors contribute to decreased biological diversity and rangeland productivity, as well as high rates of erosion, all of which are widespread problems in Tunisia (Gamoun, 2012, Tarhouni et al., 2014).…”
Section: Introductionmentioning
confidence: 99%